2023
DOI: 10.1002/fsn3.3383
|View full text |Cite
|
Sign up to set email alerts
|

Application of guar (Cyamopsis tetragonoloba L.) gum in food technologies: A review of properties and mechanisms of action

Sima Tahmouzi,
Heidar Meftahizadeh,
Saba Eyshi
et al.

Abstract: With the world continuing to push toward modernization and the consumption of processed foods growing at an exponential rate, the demand for texturizing agents and natural additives has also risen as a result. It has become increasingly common to use thickening agents in food products to modify their rheological and textural properties and enhance their quality characteristics. They can be divided into (1) animal derived (chitosan and isinglass), (2) fermentation produced (xanthan and curdlan), (3) plant fragm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(2 citation statements)
references
References 208 publications
0
2
0
Order By: Relevance
“…They are soluble in alcohol and water mixes but insoluble in water alone [ 35 ]. Unlike many other food proteins, these wheat-derived proteins are very hydrophobic, which makes it possible to encapsulate hydrophobic substances without the requirement for oily phases in the development of food-grade delivery systems [ 35 , 70 ]. Glycidin’s amphiphilic structure consists of two hydrophobic terminal domains that include several hydrophobic amino acids (phenylalanine, leucine, tryptophan, etc.)…”
Section: Natural Polymers Used For Encapsulationmentioning
confidence: 99%
“…They are soluble in alcohol and water mixes but insoluble in water alone [ 35 ]. Unlike many other food proteins, these wheat-derived proteins are very hydrophobic, which makes it possible to encapsulate hydrophobic substances without the requirement for oily phases in the development of food-grade delivery systems [ 35 , 70 ]. Glycidin’s amphiphilic structure consists of two hydrophobic terminal domains that include several hydrophobic amino acids (phenylalanine, leucine, tryptophan, etc.)…”
Section: Natural Polymers Used For Encapsulationmentioning
confidence: 99%
“…In addition, Renaldi et al [15] showed almost high sensory score ranges (6.9-7.5) for GCs formulated with 1.42:8.58% pectin-gelatin mixture. Guar gum is another natural polysaccharide derived from the seeds of the guar plant, which has been widely used in the food industry for its unique thickening, stabilizing, and emulsifying properties [16,17]. Guar gum can swell and disperse in both cold and hot water; while, other gums such as locust bean gum, disperse Pectin is one of the most popular alternative gelling agents in the production of jams and jellies, which is commonly derived from different fruits.…”
Section: Alternative Gelling Agentsmentioning
confidence: 99%